Efficiency of Commodity Futures in Price Discovery and Risk Management : An Empirical Study of Agricultural Commodities in India - Narsimhulu, Siddula; Satyanarayana, S. V. (Indian Journal of Finance, 2016)
The present study examined the efficiency of commodity futures in price discovery and risk management for agricultural commodities in India. The price discovery function was examined by using Johansen's test of cointegration (1991), vector error correction model (VECM), Wald chi-square test, and Granger causality test. The risk-management function was examined by using ordinary least squares (OLS) method and VECM to estimate optimal hedge ratio (OHR) and hedge effectiveness (HE). The study used secondary data consisting of daily closing prices of spot and futures markets for a period of 10 years (2004 – 2013) for three agricultural commodities, that is, Chana, Chilli, and Turmeric, which are traded in National Commodity & Derivatives Exchange Ltd. (NCDEX). It was found that there is a long-run association between commodity spot and futures prices of Chana, Chilli, and Turmeric. The VECM results revealed that there is a long-run causality running from futures prices to spot prices, which enable the spot market to adjust its short-run deviations from long-run equilibrium path with nearly 2.17%, 2.78%, and 4.41% speed of adjustments in Chana, Chilli, and Turmeric, respectively. The Granger causality test results revealed that there is only a unidirectional causality from futures returns to spot returns of commodities - Chilli and Turmeric. However, in the case of Chana, there is a bidirectional causality between futures and spot returns. According to hedge ratios of OLS and VECM results, it was found that the commodity futures provide 50%, 56%, and 55% variance reduction in their spot prices of Chana, Chilli, and Turmeric, respectively. It is observed that the commodity futures are more effective in hedging, and the near month futures contracts are suitable for hedging.